2021
DOI: 10.3390/polym13091505
|View full text |Cite
|
Sign up to set email alerts
|

Focused Patterning of Electrospun Nanofibers Using a Dielectric Guide Structure

Abstract: The patterning of electrospun fibers is a key technology applicable to various fields. This study reports a novel focused patterning method for electrospun nanofibers that uses a cylindrical dielectric guide. The finite elements method (FEM) was used to analyze the electric field focusing phenomenon and ground its explanation in established theory. The horizontal and vertical electric field strengths in the simulation are shown to be key factors in determining the spatial distribution of nanofibers. The experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Use of dielectric materials for gap collectors has also facilitated control of the electric field profile. Yan et al demonstrated that the relative permittivity of the collector was a key factor in controlling fiber deposition [ 13 ] and aligned fibers were achieved [ 14 ]. Liquid collectors have also been used to align fibers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Use of dielectric materials for gap collectors has also facilitated control of the electric field profile. Yan et al demonstrated that the relative permittivity of the collector was a key factor in controlling fiber deposition [ 13 ] and aligned fibers were achieved [ 14 ]. Liquid collectors have also been used to align fibers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based medicated films can be presented in the form of round or concave particles, sheets, beads-on-a-string, dumbbells, tadpoles, rods and also linear fiber films [41][42][43][44][45][46][47]. Among these morphologies, nanofibers are a special one due to their one-dimensional format, i.e., diameter at a nano scale but with a size of length at macro scale [48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%